Understanding the Meaning and Significance of Health Insurance - Dr. Radhika Kapur, (International Journal of Preventive Medicine and Health (IJPMH), 2024)
file:///D:/Desktop%20data/LSP_2/IJPMH%20Volume-3%The individuals, belonging to all communities are overwhelmed by different types of health problems and illnesses. Furthermore, within one’s lives, there are occurrences of accidents and disasters. Hence, it is of utmost significance for the individuals to acquire an efficient understanding of the meaning and significance of health insurance. The individuals are required to augment their information in terms of different types of ways that are necessary in promoting good health and wellbeing, physically as well as psychologically. Acquiring health insurance is regarded as one of the major aspects that needs to be taken into account by the individuals. The individuals are required to possess certain monthly income. The reason being, in order to make purchases of the insurance policies, the individuals are required to possess certain amount of financial resources. The reason being, they are required to pay the premium. It is normally paid for three years or five years to claim the sum on maturity. All individuals are not eligible for acquiring health insurance policies. Therefore, it is well-understood by individuals that health insurance is vital, which needs to be acknowledged by individuals. As a consequence of meeting the criteria, health insurance needs to be purchased by the individuals. In this manner, they will render an important contribution in bringing about improvements in their overall quality of lives. The main concepts that are taken into account in this research paper are, understanding the meaning and significance of health insurance, measures to be implemented in leading to up-gradation of health insurance and advantages of health insurance-5%20July%202023/B103904020124%20(24-29)/B103904020124.pdf